Intra-Aortic Balloon Occlusion (IABO) may be useful for the management of secondary aortoduodenal fistula (SADF): A case report. (2016) - Miyamoto, Kokichi; Inaba, Mototaka; Kojima, Toru; Niguma, Takefumi; Mimura, Tetsushige
Highlights: Secondary aortoduodenal fistula is one of life-threatening complication after surgical treatment for abdominal arterial aneurysm. The most important factor for acute management is controlling the bleeding from the fistula. Intra-aortic balloon occlusion may be one option for management of secondary aortoduodenal fistula. Abstract: Introduction: Secondary aortoduodenal fistula (SADF) is a rare but life-threatening complication after aortic reconstruction. Although a number of reports describing treatments for SADF have been published, the optimal management is unclear. A review of the literature suggested methods of reconstruction, control of bleeding, and reduction of infection in the management of SADF. The most important factor for acute intervention is controlling the bleeding from the fistula. We report one case treated using intra-aortic balloon occlusion (IABO) for SADF. Presentation of a case: We describe a case of secondary aortoduodenal fistula that occurred seven years following aortobifemoral reconstruction for abdominal aortic aneurysm. Discussion: Early control of bleeding is essential for survival of the patient. Emergency laparotomy or endovascular stenting frequently have been chosen as interventions, although each approach has significant limitations. Emergency laparotomy for patients with hemodynamic instability may create excessive physiologic stress, and endovascular stenting may not be available at every surgical facility. The use of IABO for cases of intraperitoneal bleeding due to trauma has been previously described. IABO is relatively easy to implement, and enabled us to control the bleeding from the aorta more rapidly than other strategies. Conclusion: Based on a review of the literature and our own experience, IABO should be considered as one option for the management of SADF.